Chemistry, manufacture and applications of natural rubber - Kohjiya, Shinzo; Ikeda, Yuko, 1956- (Woodhead Publishing in materials., 2014)
The growing demand for more sustainable materials for a variety of applications has led to increased research on the properties of natural rubber. Chemistry, manufacture and applications of natural rubber summarises this research and its significance for the industrial applications of natural rubber.